2nd international multidisciplinary microscopy and microanalysis congress: Proceedings of InterM, October 16–19, 2014 123 - Polychroniadis, Efstathios K.; Oral, Ahmet Yavuz M.; Özer, Mehmet (Springer Science and Business Media, LLC, 2015)
[No abstract available]
2nd International Multidisciplinary Microscopy and Microanalysis Congress and Exhibition, INTERM 2014 -- Oludeniz -- 153749